Ahmet Zühtü Paşa'nın hayatı ve eserleri (1834-1902) - Doğan, Kemal (My University, 2023)
Ahmet Zühtü Paşa, 19. yüzyılda, özellikle Sultan II. Abdülhamid döneminde Osmanlı maliyesinin ve maarifinin önde gelen şahsiyetlerinden biridir. Maliye bürokrasisinin en alt kademesinden başlamış ve 37 yaşında Divân-ı Muhâsebât reisliğine ve Maliye Nezareti müsteşarlığına yükselmiştir. Müsteşarlığı sırasında birçok defa görevli olarak Avrupa’ya gitmiş, devlet adına istikrâz görüşmelerinde bulunmuştur. Titizliği ve becerisiyle takdir edilerek, devletin en önemli gelir kaynaklarından olan gümrüklerin tanziminde rol almış, özellikle finansal kriz dönemlerinde dört defa maliye nazırlığına tayin edilmiştir. II. Abdülhamid döneminde mali krizlere çare bulmak üzere oluşturulan hemen hemen bütün ıslahat komisyonlarında görev almıştır. Çeşitli yerlerde mutasarrıflık ve Hüdâvendigâr vilayetinde valilik yapmıştır. Dinî konulardaki bilgisi ve Sultan II. Abdülhamid’in 1880’lerin ortasından itibaren benimsediği eğitimde İslâmî ağırlığın artırılması siyasetine uyum göstermesi nedeniyle 1891’de maarif nâzırlığına tayin edildi. Misyonerlerin kural tanımayan tutumlarına ve yeni mektepler açmalarına karşı mücadele eden Zühtü Paşa aralıksız en uzun süre bu makamda kalan maarif nâzırıdır. Kendi adıyla bilinen bir cami ve bir mektep inşa ettirmiş ve bunların masraflarını karşılamak üzere bir vakıf kurarak mülkünün önemli bir kısmını bu vakfa bağışlamıştır.

Ahmet Zühtü Pasha was one of the leading figures of Ottoman finance and education in the 19th century, especially during the reign of Sultan Abdülhamid II. He started at the lowest level of the finance bureaucracy and he was promoted to the position of head of the Divân-ı Muhâsebât (Court of Accounts) and undersecretary of the Ministry of Finance at the age of 37. During his undersecretariat, he traveled to Europe many times on assignment and negotiated loans on behalf of the state. Appreciated for his meticulousness and skill, he took part in the organization of customs, one of the most important sources of income for the state, and was appointed as finance minister four times, especially during periods of financial crisis. He took part in almost all reform commissions formed to find a solution to the financial crises during the reign of Abdülhamid II. He served as mutasarrıf (governor of a subdivision of a province) in various places and as governor in the province of Hüdâvendigâr. He was appointed as the minister of education in 1891 due to his knowledge of religious issues and his compliance with the policy of increasing the Islamic weight in education adopted by Sultan Abdülhamid II since the mid-1880s. Zühtü Pasha, who fought against the unruly behavior of missionaries and their opening of new schools, was the longest-serving minister of education. He built a mosque and a school known by his name and established a foundation to cover their expenses, donating a significant portion of his property to this foundation.
Keywords: Abdulhamid II; Ahmet Zühtü Paşa (1834-1932); Finance, Public; Governor of Bursa; History; Hüdavendigâr Valisi; II. Abdülhamid; Maarif Nezâreti; Maliye Nezâreti; Maliye, Kamu; Ministry of Education; Ministry of Finance; missionaries; misyonerler Zuhdi Pasha; Osmanlı Borçları; Osmanlı muhasebeciliği; Ottoman accountancy; Ottoman Debts; Reorganization; Tanzimat; Tarih; Turkey; Türkiye; Zühtü Paşa